Climate security policy coherence and awareness analysis: Philippines - Schapendonk, Frans; Scartozzi, Cesare Marco; Meddings, George; Melgar, Adriana; Laderach, Peter; Pacillo, Grazia (2024)
This policy coherence and awareness analysis (PCAA) report systematically analyses 41 policies and strategic frameworks produced by the Philippine national government and relevant regional bodies in the Asia-Pacific region to assess the extent to which climate-related security risks are currently accounted for in policy and planning. We find that connections between climate change, human (in)security, and conflict remain generally underexplored. When such risks are identified, they are predominantly identified in the context of fast-onset climate impacts as opposed to slow-onset climate impacts. Several key demographic groups that are likely to be particularly exposed to climate-related security risks are moreover underrepresented within Philippine policy discourse, including small-holder farmers in post-conflict areas. Finally, we find limited evidence of cross-sectoral and cross-scalar integration amongst the policy sectors deemed critical for the coherent management of climate-related security risks. This paper concludes with a set of targeted recommendations for Philippine policy and decision-makers on how to further mainstream climate, peace, and security.